In Silico Comparison of Main Proteinase Inhibitors for Different Coronaviruses (Baghdad Science Journal, 2024)
AbstractCoronaviruses are enclosed positive stranded RNA viruses with spike protein protrusions that permit the virus to penetrate and affect host cells. The emergence of Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV) and Middle East Respiratory Syndrome Coronavirus (MERS-CoV), as mortal human CoV illnesses, has sparked considerable interest in the medical community. The fast and global outbreak of a novel human coronavirus generated by a novel progeny of coronavirus 2 (CoV-2) has promoted an urgent need to identify an effective target for COVID-19 treatment. The main proteinase MPro has been prominented as an appealing therapeutic target for coronaviruses, which is responsible for the transcriptase and replicase of coronaviruses. The identification of prospective medications is an imperative and critical need for the medical community. Molecular docking was used to describe the protease and asses the capacity of various well-known and laboratory-tested natural MPro inhibitors. Seventy-sixth natural compounds with known inhibitory activity and four medicines reported against CoV-1 were chosen for molecular docking study.  Our in-silico studies reveal that many of these molecules show high binding affinity for several CoV-2 proteases and compare favorably to CoV-1 and MERS proteases. Our research indicates that these molecules could be anti CoV-2 MPro. implying their possibility for reprofiling as antiviral leads with broad scope.